2012
DOI: 10.1016/j.envpol.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between aging of PAHs and soil properties

Abstract: Hard organic carbon Porosity Diffusion a b s t r a c t Sequestration and diffusion of three polycyclic aromatic hydrocarbons (PAHs) in seven Chinese soils were investigated for up to 200 days in sterile soil microcosms as functions of soil property and aging time. The aging of the PAHs, assessed using a mild extractant that removes primarily the labile fraction, showed a biphasic behavior. The rapid diffusion from labile to nonlabile domains was mainly dependent upon the distribution of meso-and micropore frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 32 publications
3
83
2
Order By: Relevance
“…This 17 was opposed to the inverse proportionality, reported in the majority of studies, between 18 the OC content of a soil and the extractability of the sorbed contaminants. This 19 phenomenon could be due to a higher microporosity of soils with low OC content 20 (Ncibi et al 2007;Luo et al 2012), and/or to differences in the quality of their OM. 21 The different microporosity of the three soils studied is not likely the cause of such 22 behaviour because, as observed in Table SD2, microporosity follows the sequence: soil 23 3 > soil 2 > soil 1.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…This 17 was opposed to the inverse proportionality, reported in the majority of studies, between 18 the OC content of a soil and the extractability of the sorbed contaminants. This 19 phenomenon could be due to a higher microporosity of soils with low OC content 20 (Ncibi et al 2007;Luo et al 2012), and/or to differences in the quality of their OM. 21 The different microporosity of the three soils studied is not likely the cause of such 22 behaviour because, as observed in Table SD2, microporosity follows the sequence: soil 23 3 > soil 2 > soil 1.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…The aqueous solubility and, as a consequence, the bioavailability of PAHs decrease with increasing number of aromatic rings (Peng et al 2008). In addition, many studies have demonstrated that the extractability and the bioavailability of PAHs decrease significantly with time in the aging processes (Northcott and Jones 2001;Luo et al 2012). Most PAHs released into the environment will finally enter into the soil ecosystem, where they will impair human and other organisms through the food chain (Fismes et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Total C and N were measured with an elemental analyzer (PE2400, PerkinElmer Inc.). Total organic C was determined after acid treatment (10% HCl) to remove inorganic C, and DOC was extracted with 0.01 mol L −1 NaCl at a soil to solution ratio of 1:20 for 6 h (Luo et al, 2012). Total S was determined by ICP-AES after digestion with a mixture of HNO 3 and HClO 4 (85:15 v/v) (Zhao and McGrath, 1994).…”
Section: Sampling and Sample Pretreatmentsmentioning
confidence: 99%